Redesain Map Rekam Medis Di Puskesmas Medan Johor - Esraida Simanjuntak; Valentina; Mei Sryendang Sitorus; Azizah Putri Syafa Harahap (Indonesian Journal of Health Information Management Services, 2022)
Map is a thick paper cover used to store medical record sheets, which serves to unite all patient sheets so that they become a unified whole history, protect the medical record files in it so they are not easily damaged, torn and folded. as well as facilitate storage, search and transfer. medical record file. The purpose of this community service is to redesign the medical record folder in terms of anatomy, physicality and content, as well as the boundaries of form between forms of family members (father, mother and child) at the Medan Johor Health Center. The community service methods used are public education, consultation, and the diffusion of science and technology. This service activity was carried out for 4 months. The result of this community service activity is a product in the form of a medical record folder (folder) at the Medan Johor Health Center.